Planning simulation space needs in uncertain contexts. (8th May 2019) - Tann, Catherine; Bates, Richard
Abstract : Introduction: King's College London delivers simulation-based education to approximately 5500 different students who use a Simulation and Interactive Learning (SaIL) centre which was designed for significantly different needs. The management team needs to plan for current and future demand in the context of changing regulatory and curricular requirements, and changing technologies. The authors developed a model to address this challenge. Methods: We used a structured approach involving university data and interviews with module leaders. Assumptions were needed on target student numbers, group sizes and time spent in a simulation centre. The algorithm at the core of the model applies the targets and assumptions to a profile of room use by type of room, as experienced by a typical student over the course of one year. Individual course results are summed and rounded up, to provide an overall demand for space which can be compared to capacity. Results: The number of SaIL rooms required is expected to almost double by 2022/2023. The mix of spaces must also change to enable more simultaneous immersive simulation of diverse types, with associated debrief spaces also increasing. Conclusions: This model helps maximise impact by creating connectivity between a vision, business targets and the physical space. Financial resources are used more effectively by avoiding potential over or underprovision. Flexibility of build will remain important, as no-one can predict the future; however, a detailed, quantified model can help raise the quality of discussion about future aspirations and how closely we might meet them.